Strong sensitivity of watershed-scale, ecohydrologic model predictions to soil moisture. (October 2021) - Pignotti, Garett; Rathjens, Hendrik; Chaubey, Indrajeet; Williams, Mark; Crawford, Melba
Abstract: It is currently unclear how changes to modeled soil water simulations influence key predictions in complex, ecohydrologic models, particularly beyond hydrology. We assessed sensitivity to soil moisture in the Soil and Water Assessment Tool by artificially perturbing simulated soil moisture and analyzing targeted prediction change. Results demonstrated a strong, process-dependent sensitivity of model predictions to perturbations in soil moisture. At the basin scale, the absolute values of differences from a baseline simulation for surface runoff, evapotranspiration, and nitrate loss ranged from 42% to 107%, 29%–76%, and 19%–369%, respectively, for soil moisture changes between 0.5 and 2 standard deviations. Landscape-scale results illustrated the impact of modeled land management actions, notably fertilizer applications, on determining the magnitude of the change. The findings highlight and motivate the need to improve soil moisture simulations, suggesting possible accuracy improvement for key model predictions by more precisely simulating soil moisture. Graphical abstract: Image 1 Highlights: Soil and Water Assessment Tool sensitivity to soil moisture was tested. A strong impact on model predictions due to soil moisture change was demonstrated. Sensitivity varied by targeted outputs based on their linked model processes. Modeled land management was influential in nutrient/plant prediction sensitivity. The findings show the need for accurate soil water dynamics in ecohydrologic models.